HOW TO DEVELOP THE TRANSLATION METHOD IN EFL CLASSES (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The methodology further develops students' general skills to notice and observe details of language systems, cultures and societies to convey messages between two languages. The practical significance of the study lies in the fact that the introduction of the translation method can expand foreign language teaching beyond the classroom.